1995
DOI: 10.1037/0022-3514.69.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Transference in social perception: The role of chronic accessibility in significant-other representations.

Abstract: Research has shown that the activation and application of a significant-other representation to a new person, or transference, occurs in everyday social perception (S. M. Andersen & A. Baum, 1994; S. M. Andersen & S. W. Cole, 1990). Using a combined idiographic and nomothetic experimental paradigm, two studies examined the role of chronic accessibility of significant-other representations in transference. After learning about 4 fictional people, 1 of whom resembled a significant other, participants' recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
228
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(243 citation statements)
references
References 110 publications
(216 reference statements)
12
228
1
2
Order By: Relevance
“…Reacţia la trăsăturile observabile evidenţiază atractivitatea fizică (White, 1980), (Regan, 1998) ce angajează raporturi interpersonale (Abel, & Watters, 2005), (Baron & Byrne, 1997), replica simbolică adresată partenerului reflectând transferul identitar simbolic proiectat asupra celui evaluat (Andersen et al, 1995).…”
Section: Problem Statementunclassified
“…Reacţia la trăsăturile observabile evidenţiază atractivitatea fizică (White, 1980), (Regan, 1998) ce angajează raporturi interpersonale (Abel, & Watters, 2005), (Baron & Byrne, 1997), replica simbolică adresată partenerului reflectând transferul identitar simbolic proiectat asupra celui evaluat (Andersen et al, 1995).…”
Section: Problem Statementunclassified
“…One study found that people who tend to trust their intuitions tend to make stronger implicit associations between an attitudinally similar stranger and "family" concepts, but not the broader category of "pleasant" concepts (Park & Schaller, 2005). Social psychological studies have shown that people possess rich mental representations of significant individuals (e.g., parent, sibling, spouse), and when presented with a novel target who resembles a significant individual, information processing of the target is influenced by those existing representations (Andersen, Glassman, Chen, & Cole, 1995). For example, after meeting a person who reminds me of my brother, I might mistakenly remember that the person likes to watch science fiction films because my brother does.…”
Section: Park and Ackerman 14mentioning
confidence: 99%
“…First, because being a leader is socially attractive (Hogg, 2001), leaders are often scrutinized by employees who try to decipher their behavior (Lord, Brown, & Freiberg, 1999). Second, previous studies suggest that aspects of a follower's self-concept can be activated by the leader and that this information strongly guides self-perceptions and reactions (e.g., Andersen et al, 1995;Ritter & Lord, 2007). Importantly, the identity (Harré, 1983) and social comparison (Festinger, 1954) literature also suggests that self-comparisons with successful others trigger motivation to acquire leadership skills, especially if the individual perceives some similarity with the subject of comparison (Buunk & Gibbons, 2007;Greenberg et al, 2007, Kilduff, 1990.…”
Section: Types Of Self-to-role Comparisons and The Motivation To Leadmentioning
confidence: 99%
“…Therefore, when evaluating their own capacities for leadership positions, people usually use specific individuals who already made it (Buunk & Gibbons, 2007). Research has shown that the alignment of the self with the leadership role in terms of skills, knowledge and behaviors occurs, to a large extent, through these upward comparisons with specific individuals or role models (Gibson, 2003) that are particularly important to identify specific knowledge (Andersen et al, 1995), understand the idiosyncratic behaviors and skills associated with the role (Bandura, 1977), and look for manifest signs of effective performance and calibrate someone's capabilities to succeed (Greenberg, Ashton-James, & Ashkanasy, 2007).…”
Section: Types Of Self-to-role Comparisons and The Motivation To Leadmentioning
confidence: 99%
See 1 more Smart Citation